Утицај промена у серумским нивоима ИЛ-1Ф4, ИНЦАМ-1 и ВПФ на пацијенте са дијабетичком ретинопатијом: Серумски ИЛ-1Ф4, ИНЦАМ-1 и ВПФ код дијабетичке ретинопатије - Xie, Tianyang; Lu, Qianyi; Zhu, Wei; Huang, Dan (Journal of Medical Biochemistry, 2026)
[Objective] To explore the relationships between serum Interleukin-1 family member 4 (IL-1F4), Intercellular adhesion molecule-1 on endothelial cells (INCAM-1), and Vascular Permeability Factor (VPF) levels and disease progression and prognosis in patients with diabetic retinopathy (DR).[Methods] 538 individuals with type 2 diabetes mellitus (T2DM) who were admitted to our hospital between February 2022 and February 2025 were chosen retrospectively. Based on their DR consequences, these patients were split into two groups: 178 cases of T2DM and 360 cases of DR. The evolution of these DR patients' illnesses led to further division into two groups: a non-PDR (NPDR) group (134 instances) and a proliferative DR (PDR) group (226 cases). Additionally, 134 healthy volunteers who underwent examinations throughout the same time frame made up the control group. The differences in clinical data and serum levels of IL-1F4, INCAM-1, and VPF among the different groups were compared; the correlations among serum levels of IL-1F4, INCAM-1, and VPF were analyzed, and to determine the variables affecting the course of DR. Based on the occurrence of visual impairment, DR patients were divided into two groups after a year of follow-up: those with a favorable prognosis (256 patients) and those with a poor prognosis (104 patients). Differences in clinical data and serum levels of IL-1F4, INCAM-1, and VPF among DR patients with different prognoses were compared. The factors influencing the poor prognosis of diabetic retinopathy (DR) were identified using multivariate logistic regression analysis, and the predictive value of serum IL-1F4, INCAM-1, and VPF for the poor prognosis of DR was assessed using receiver operating characteristic (ROC) curves.[Results] The fasting blood glucose (FPG), glycosylated hemoglobin (Hb A1c), IL-1F4, INCAM-1, and VPF levels in the control group, T2DM group, NPDR group, and PDR group increased successively (P < 0.05), and the duration of diabetes in the T2DM group, NPDR group, and PDR group increased successively (P < 0.05). The serum levels of IL-1F4, INCAM-1, and VPF in individuals with DR showed positive relationships (r = 0.500, 0.489, and 0.564, respectively; P < 0.05) according to Pearson analysis. High levels of FPG, Hb A1c, IL-1F4, INCAM-1, and VPF, together with a longer duration of diabetes, were all found to influence the advancement of DR (P < 0.05) by multivariate logistic regression analysis. Groups with poor prognoses were older than those with good prognoses. Body mass index, FPG, Hb A1c, IL-1F4, INCAM-1, and VPF were higher in the group with a bad prognosis than in the group with a good prognosis. Additionally, the duration of diabetes was longer in the poor prognosis group (P < 0.05). Multivariate logistic regression analysis revealed that a longer duration of diabetes, as well as high levels of FPG, Hb A1c, IL-1F4, INCAM-1, and VPF, were all variables affecting how DR progressed (P < 0.05). The areas under the curve (AUCs) for forecasting a bad prognosis in individuals with diabetic retinopathy (DR) were found using ROC curve analysis. according to serum levels of IL-1F4, INCAM-1, and VPF were 0.771, 0.823, and 0.766, respectively. When these three indicators were combined, the area under the curve (AUC) for predicting a poor prognosis in DR patients was 0.873, which was higher than the AUC for any one sign alone (P < 0.05).[Conclusion] Serum IL-1F4, INCAM-1 and VPF may jointly participate in the process of DR. The elevated levels of these cytokines are closely related to the progression of DR and poor prognosis. Serum IL-1F4, INCAM-1 and VPF can be used as effective indicators for evaluating the progression of DR and visual disability.